Open defecation in the world - Mora-Alvarado, Darner (2024)
This study describes the evolution of Safely Managed Sanitation (SMFS) coverage, defined as “the use of improved facilities that are not shared with other households and where excrement is safely disposed of on site or disposed of with off-site treatment” by Sustainable Development Goals (SDG) regions, by country groups according to economic income and by development or fragility groups. Furthermore, on the contrary, because the goal of the SDGs is to eliminate the practice of open defecation (OLD), the evolution of the decrease is described, between the years 2015 and 2022, in the same groupings indicated. The results obtained from the WHO/UNICEF Joint Monitoring Program (JMP) indicate that globally SGFS coverage went from 49 to 57% in the afore mentioned period. For its part, the DAL fell from 10% to 5% worldwide, equivalent to some 433 million inhabitants, this without taking intoaccount the 281 million migrants who use DAL on their journey, more out of physiological necessity than out of cultural custom. Given this, the agreement between the level of income and the use of SGFS and the DAL is evident.